FABS (FORMULATED ABSTRACTING): AN EXPERIMENT IN REGULARIZED CONTENT DESCRIPTION / (FABS: UNE ETUDE POUR LA FORMALISATION DU RESUME SIGNALETIQUE) - Harris, Brian; Hofmann, Thomas R. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2022)
see PDF